Luminescence and scintillation properties of Gd3Sc2(Al3-xGax)O12:Ce (x = 1, 2, 3) garnet crystals. (October 2021) - Chewpraditkul, Warut; Pattanaboonmee, Nakarin; Chewpraditkul, Weerapong; Sakthong, Ongsa; Kim, Kyoung Jin; Yoshino, Masao; Horiai, Takahito; Kurosawa, Shunsuke; Yoshikawa, Akira; Kamada, Kei; Drozdowski, Winicjusz; Witkowski, Marcin E.; et al.
Abstract: The luminescence and scintillation characteristics of Ce 3+ - doped Gd3 Sc2 (Al3-x Gax )O12 (x = 1, 2, 3) garnet crystals were investigated. The Ce 3+ luminescence was blue-shifted with increasing Ga content due to the decrease of the crystal field strength. A decrease of Ce 3+ luminescence intensity and luminescence decay time at high temperature was observed for all samples due to thermal ionization of the Ce 3+ 5d1 excited levels. With increasing Ga content the decrease of thermal activation energies, determined from temperature dependence of decay times, was obtained. Both Gd3 Sc2 Al2 GaO12 :Ce and Gd3 Sc2 AlGa2 O12 :Ce samples exhibited a comparable light yield (LY) value of 24, 000 photons/MeV while the latter sample showed faster scintillation decay time of 12 ns (11%) + 56 ns (89%) with respect to those of 55 ns (28%) + 105 ns (72%) for the former sample. An acceleration of scintillation decay time with an expense of LY value was also obtained for the Mg 2+ -codoped sample. At low temperature a decrease of scintillation yield was observed in correlation with the intense thermoluminescence peaks, attributing to the localization of electrons at intrinsic shallow traps. Highlights: Scintillation properties of Gd3 Sc2 (Al3-x Gax )O12 (x = 1, 2, 3) were investigated. Temperature dependences of RL yield and PL decay time were measured. Thermal activation energy decreased with increasing Ga content. Luminescence quenching at RT was obtained due to thermal ionization. Low-temperature thermoluminescence was investigated.